Impact of comorbidity on the predictive value of cystatin-C in patients admitted for acute decompensated heart failure: insights from a prospective study. (25th November 2020) - Kayama, K; Yamada, T; Watanabe, T; Morita, T; Furukawa, Y; Tamaki, S; Kawasaki, M; Kikuchi, A; Kawai, T; Seo, M; Nakamura, J; Kawahira, M; et al.
Abstract: Background: Comorbidities are strongly associated with poor clinical outcome in heart failure patients. The Age-adjusted Charlson comorbidity index (ACCI), which is well-known widely used comorbidity index, recently has been used as a robust prognostic model in heart failure patients. On the other hand, Cystatin C, as a novel and important biomarker of renal function, has been recently reported as a useful long-term risk stratification score in heart failure patients. However, there is no information available on the impact of comorbidities on the prognostic value of cystatin-C in patients admitted for acute decompensated heart failure (ADHF). Methods: We prospectively studied 458 consecutive ADHF patients with survival discharge. Patients with hemodialysis were excluded. Echocardiography and venous blood sampling were performed just before discharge and serum cystatin-C level was measured. Comorbidity was measured with the Age-adjusted Charlson comorbidity index (ACCI). ACCI was commonly used for the evaluation of the comorbid condition which is weighted and scored, with additional points added for age. The endpoint was all-cause death (ACD). Results: During a follow-up period of 2.8±1.5 years, 132 patients had ACD. At multivariate Cox analysis, ACCI (p=0.0015) and cystatin-C level (p=0.0145) were significantly and independently associated with ACD. Patients with high ACCI (≥6: determined by ROC analysis) had a significantly greater risk of ACD (37.2% vs 17.8%, p<0.0001, HR 2.45 [1.61–3.70]). In the subgroup of higher ACCI, patients with higher cystatin-C level (≥1.56: determined by ROC analysis) had a significantly higher risk of ACD (50.3% vs 23.4%). Furthermore, in the subgroup of lower ACCI, patients with higher cystatin-C level had also significantly higher risk of ACD (34.2% vs 12.1%). Conclusions: The prognostic value of cystatin-C is not affected by comorbidities and cystatin-C provide prognostic information even in patients admitted for ADHF, irrespective of comorbid burden. Funding Acknowledgement: Type of funding source: None